2020
DOI: 10.1186/s12940-020-00662-2
|View full text |Cite|
|
Sign up to set email alerts
|

Immune biomarkers link air pollution exposure to blood pressure in adolescents

Abstract: Background Childhood exposure to air pollution contributes to cardiovascular disease in adulthood. Immune and oxidative stress disturbances might mediate the effects of air pollution on the cardiovascular system, but the underlying mechanisms are poorly understood in adolescents. Therefore, we aimed to identify immune biomarkers linking air pollution exposure and blood pressure levels in adolescents. Methods We randomly recruited 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 70 publications
0
26
1
Order By: Relevance
“…Monocytes are key white blood cells of the innate immune system and play a central role in inflammasome activation and cardiovascular diseases. Exposure to NO 2 was positively associated with monocyte levels and diastolic blood pressure after full adjustment 106 . Thus NO 2 may promote monocyte enrichment and DNA methylation in monocytes, which subsequently affects diastolic blood pressure and ultimately aggravates COVID‐19.…”
Section: Effect Of Pollutant Exposure On Covid‐19mentioning
confidence: 98%
See 3 more Smart Citations
“…Monocytes are key white blood cells of the innate immune system and play a central role in inflammasome activation and cardiovascular diseases. Exposure to NO 2 was positively associated with monocyte levels and diastolic blood pressure after full adjustment 106 . Thus NO 2 may promote monocyte enrichment and DNA methylation in monocytes, which subsequently affects diastolic blood pressure and ultimately aggravates COVID‐19.…”
Section: Effect Of Pollutant Exposure On Covid‐19mentioning
confidence: 98%
“…87,99 In addition, high-level NO 2 exposure can induce endothelial dysfunction and oxidative stress disturbances. 106 Thus, it is possible that NO 2 exposure contributes to inflammation and immune disorders and exacerbate SARS-COV-2-induced lung damage.…”
Section: Effect Of Pollutant Exposure Onmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are not restricted to adult populations, as indicated by a recent study from Mann et al that indicates that acute increases in traffic related air pollutants were associated with 8-isoprostane levels in 299 children (aged 6–8) [ 22 ]. Likewise, adolescents ( n = 100) were demonstrated to be a susceptible group, by showing that exposure to multiple air pollutants was related to markers of oxidative stress, acute inflammation, altered hemostasis, endothelial dysfunction, monocyte enrichment, and high blood pressure [ 23 ]. In a larger cohort of 3996 subjects, Li et al found acute increases in PM 2.5 and sulfate to be associated with increased C-reactive protein levels, which was also true for nitrogen dioxide (NO 2 ) in the case of interleukin (IL)-6, and for black carbon (BC), sulfate, and ozone (O 3 ) in the case of tumor necrosis factor receptor 2 [ 24 ].…”
Section: Pathomechanisms Of Air Pollution With Focus On Oxidative Stress and Inflammationmentioning
confidence: 99%